Case report: Xeroderma pigmentosum Group A with erythropoietic protoporphyria in a young Chinese patient - Wu, Shu-hui; Xiao, Ting; Zhao, Dan; Zeng, Ying-hong; Zhu, Ming-fang (Frontiers in Endocrinology, 2024)
Xeroderma pigmentosum, is a rare autosomal recessive genodermatoses characterized by the deficiency in nucleotide excision repair. Erythropoietic protoporphyria, is a rare inherited metabolic disease caused by the perturbation of heme. Xeroderma pigmentosum-erythropoietic protoporphyria is exceedingly rare.Hereby, we firstly report a young Chinese case of xeroderma pigmentosum Group A with erythropoietic protoporphyria carrying the XPA Met214AsnfsTer7 frameshift mutation and the homozygous splicing mutation, c.315-48T>C in the proband's intron3 of FECH.